Progressive Advance in Supply chain management of Regional Socio-Economic Development: Conceptual Framework and Evaluation Mechanism - Yuliya Pavlovna Soboleva; Vladimir Vladimirovich Matveev; Irina Borisovna Ilyukhina; Irina Sergeevna Efimenko; Sergei Vadimovich Simonov (International Journal of Supply Chain Management, 2019)
At present, a large number of methodologies have been developed aimed at assessing and forecasting the potential of the socio-economic development of certain regions. It should be noted that human and social capabilities as the key elements of regional development are currently the least studied issues. Therefore, in this work, along with economic factors, considerable attention is paid to the assessment of human potential and the social component of the workforce. Unlike political, economic and investment factors, these elements are subject to changes in the short-run, and are engines of regional development and the most promising of its components. The purpose of the study is to develop a mechanism for assessing the level of regional development and identifying factors affecting this process. The implementation of this procedure in practice is especially significant when planning and adjusting activities related to regional management. Deepening and developing previous studies, in this paper we synthesize known approaches to assessing regional socio-economic development, offer our own set of criteria for evaluating advancements and test the developed approach as exemplified by the regions of the Central Federal District in Russia. The scientific novelty of the study is that to assess the regional socio-economic development we propose evaluation of the level of advancement. To do this, all the indicators included in the model are considered dynamically and are evaluated by the corresponding indices. Such an approach will make it possible to assess the prospects for the development of the factor under study and make timely adjustments to the regional policy. The objects of research in this paper are the regions of the Central Federal District in Russia. The subjects of the study are the factors that cause advancements in regional economic development. The following research methods are used: retrospective analysis, statistical observation method, correlation analysis, principles and methods of system analysis and, computational procedures based on the use of financial mathematics and financial management tools.